Analyse The Impact of Financial Management on Public Growth - Shrikant, Dr. Anivilla; Lepcha, Dawakit (International Journal of Accounting and Economics Studies, 2025)
This study investigates the influence of financial management practices on public sector growth, focusing specifically on Indian government ministries. It examines how budgeting, financial planning, and internal control mechanisms contribute to financial performance and policy effectiveness. While small and medium-sized enterprises (SMEs) are briefly referenced in the literature context, the core empirical focus of this study is on ministries rather than SMEs. Data was collected from 226 respondents across central government directorates and analyzed using SPSS tools. The findings provide actionable insights for public financial management reform and support inclusive financial governance in India.
Keywords: Financial Management Practices; Agency Cost; SMES; Working Capital